The use of Cattapa Leaves Terminalia cattapa as Preventive and Curative Methods in Patin Catfish Pangasionodon hypophthalmus Infected With Aeromonas hydrophila - Wahjuningrum, D.; Ashry, N.; Nuryati, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
Motile Aeromonad Septicaemia (MAS) caused by Aeromonas hydrophila induced serious epidemics of ulcerative disease in freshwater fish including patin catfish Pangasionodon hypophthalmus. In vitro study for antibacterial test of cattapa leaves Terminalia cattapa (TC) were done previous to the in vivo test. The in vitro susceptibility test was performed at the dosages of 30, 60 and 90 g/l TC. At the in vivo test, fish were injected intramusculary with TC at the dosages of 60 g/l for the prevention and 120 g/l for curative efficacy. Results from blood picture, clinical sign and mortaliyt showed that TC were better and more effective as preventive than curative for MAS in patin catfish. Keywords : Terminalia cattapa, Aeromonas hydrophila, patin catfish ABSTRAK Penyakit MAS (Motile Aeromonad Septicaemia) yang disebabkan oleh Aeromonas hydrophila sering menyebabkan wabah penyakit tukak pada ikan-ikan air tawar termasuk pada ikan patin Pangasionodon hypophthalmus. Uji antibakteri secara in vitro dari daun ketapang Terminalia cattapa (TC) dilakukan sebelum uji in vivo. Pada uji in vitro dilakukan pengujian aktivitas antibakteri TC terhadap A. Hydrophila pada dosis TC 30, 60 dan 90 g/l. Pada uji in vivo, ikan diinfeksi secara intramuskular dengan TC, untuk pencegahan dengan dosis 60 g/l TC dan pengobatan pada dosis 120 g/l TC. Hasil yang diperoleh dari gambaran darah, gejala klinis dan kematian ikan patin menunjukkan bahwa TC lebih baik dan sangat efektif untuk pencegahan daripada pengobatan untuk penyakit MAS pada ikan patin. Kata kunci: Terminalia cattapa, Aeromonas hydrophila, ikan patin